Pengaruh Motivasi Dan Budaya Organisasi Terhadap Kinerja Karyawan Pt Lexxa Data Indonusa - Dion Tri Pranada Setiawan; Heru Sutapa; Nuraidya Fajariah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study explains the effect of word motivation and organizational culture on the performance of employees of PT Lexxa Data Indonusa Tulungagung. The analysis technique in this study used validity test, reliability test, classical assumption test, multiple linear regression test and hypothesis test and the samples used in this study were 46 employees at PT Lexxa Data Indonusa Tulungagung. From the results of the analysis that has been done, it shows that work motivation has no partial and significant effect on employee performance, but organizational culture has a partial and significant effect on employee performance. Work motivation and organizational culture simultaneously influence the performance of PT Lexxa Data Indonusa Tulungagung employees.